2022
DOI: 10.3846/jbem.2022.16094
|View full text |Cite
|
Sign up to set email alerts
|

Oil Price Volatility and Airlines’ Stock Returns: Evidence From the Global Aviation Industry

Abstract: The paper explores the long versus short-term attributes of the airline industry exposure to oil price risk in a macroeconomic framework that emphasizes the interconnections between various risk factors, which is the main contribution to the research in the field. A panel ARDL model and PMG estimator have been applied on monthly data between 2007 and 2020 to investigate the long-term equilibrium relationship between airline companies’ stock prices, oil price risk, financial market volatility, currency risk, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…This theory is supported by the fundamental idea that oil functions as a crucial input for various industries. Consequently, any upsurge in oil prices is projected to elevate operational expenses, leading to a decrease in forthcoming cash flows, profits, and dividends, affecting stock prices and returns (Horobet et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This theory is supported by the fundamental idea that oil functions as a crucial input for various industries. Consequently, any upsurge in oil prices is projected to elevate operational expenses, leading to a decrease in forthcoming cash flows, profits, and dividends, affecting stock prices and returns (Horobet et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Based on these results, the research provided recommendations and proposals for investors and stakeholders in the financial market. Horobet et al (2022) looked into the impact of oil price volatility on airline stock returns. The study used panel ARDL models and PMG estimators to examine the risks associated with oil prices and aviation stock prices having a long-term equilibrium relationship, financial market volatility, exchange rates, inflation, and maturity risk from 2007 to 2020.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis revealed that the airline industry experienced a decrease in stock price returns due to changes in crude oil prices between 2008-2009 (Shaeri et al, 2016) research shows that the price of crude oil has a greater impact on the stock price of airlines compared to other industries. According to (Yashodha et al, 2017), The drop in crude oil prices had a detrimental effect on Cathay Pacific Airways Limited and China Airlines (Kristjanpoller & Concha, 2016) also discovered a positive impact on 56 airline companies (Horobeț et al, 2022) reported that the crude oil price had an effect on five US airlines. (Xiao & Yoon, 2019) I studied the influence of three different crude oil prices on the stock prices of four airlines using VAR-GARCH.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Technologies that improve fuel efficiency are needed in this stagnant market to reduce airline operation costs and accelerate the industry's recovery. Moreover, as global warming continues to intensify, IATA aimed for a 50% reduction of net carbon emissions in the industry by 2050, revealing the importance and urgency of increasing fuel efficiency [9]. Based on research, around 85% of drag in today's commercial aircraft comes from skin friction and induced drag, highlighting the importance of further investigation in both fields [10].…”
Section: Introductionmentioning
confidence: 99%